Cochlear Implantation in Sporadic Vestibular Schwannoma and Other Retrocochlear Pathology: A Case Series. Issue 4 (April 2021) - Patel, Evan J.; Deep, Nicholas L.; Friedmann, David R.; Jethanamest, Daniel; McMenomey, Sean O.; Roland, John Thomas
Abstract : Objective: To describe outcomes with cochlear implantation (CI) for rehabilitation of hearing loss in patients with sporadic vestibular schwannomas (VS) and other retrocochlear pathologies. Study Design: Retrospective review. Setting: Tertiary-care center. Patients: Twenty three cases in 19 patients (53% men, mean age 55.8 yr) with non-neurofibromatosis type 2 related retrocochlear pathology. Interventions: Unilateral or bilateral CI. Main Outcome Measures: Word recognition score, device usage. Results: Etiology of deafness included sporadic VS (n = 9, 39%), radiation after head and neck or central nervous system (CNS) malignancy (n = 8, 35%), superficial siderosis (n = 3, 13%), neurosarcoidosis (n = 2, 9%), and pontine stroke (n = 1, 4%). Mean follow-up duration was 2.3 years (standard deviation [SD] 3.0; range, 0.2–9.4). Auditory perception was achieved in 20 out of 22 patients (91%) who have been activated. Mean WRS in patients with sporadic VS was 18% (SD 20; range, 0–44). Mean WRS in patients with non-VS retrocochlear pathology was 55% (SD 30; range, 0–94). Data logs showed 7.0 h/d of average use (SD 4.3; range, 0–13). Conclusions: Appropriately selected patients with retrocochlear pathology may benefit from CI so long as the patient has a cochlear fluid signal and an intact cochlear nerve. Patients with sporadic VS patients and normal contralateral hearing exhibited guarded outcomes with CI, whereas most patients with non-VS retrocochlear pathologies demonstrated open-set speech understanding scores comparable to or slightly worse than conventional CI candidates. Since variable performance benefit is observed with CI in patients with retrocochlear pathology, counseling is imperative to align patient expectations with realistic outcomes.